Health risks due to pre-harvesting sugarcane burning in São Paulo State, Brazil - Maria Leticia de Souza Paraiso; Nelson Gouveia (Revista Brasileira de Epidemiologia, 2015)
After 2003, a new period of expansion of the sugarcane culture began in Brazil. Pre-harvesting burning of sugarcane straw is an agricultural practice that, despite the nuisance for the population and pollution generated, still persisted in over 70% of the municipalities of São Paulo State in 2010. In order to study the distribution of this risk factor, an ecological epidemiological study was conducted associating the rates of deaths and hospital admissions for respiratory diseases, for each municipality in the State, with the exposure to the pre-harvesting burning of sugarcane straw. A Bayesian multivariate regression model, controlled for the possible effects of socioeconomic and climate (temperature, humidity, and rainfall) variations, has been used. The effect on health was measured by the standardized mortality and morbidity ratio. The measures of exposure to the pre-harvesting burning used were: percentage of the area of sugarcane harvested with burning, average levels of aerosol, and number of outbreaks of burning. The autocorrelation between data was controlled using a neighborhood matrix. It was observed that the increase in the number of outbreaks of burning was significantly associated with higher rates of hospital admissions for respiratory disease in children under five years old. Pre-harvesting burning of sugarcane effectively imposes risk to population health and therefore it should be eliminated.